Effectively promoted catalytic activity by adjusting calcination temperature of Ce‐Fe‐Ox catalyst for NH3‐SCR. (23rd December 2019) - Song, Zhongxian; Xing, Yun; Zhang, Tingji; Zhao, Jinggang; Wang, Junkai; Mao, Yanli; Zhao, Baolin; Zhang, Xuejun; Zhao, Min; Ma, Ziang
Abstract : A series of Ce‐Fe‐O x catalysts prepared by the different calcination temperatures (marked as CF‐ X, where X represented calcination temperature) were used to the selectivity catalytic reduction of NO x by NH3 . The results explained the relationship between calcination temperature and the sulfate species over Ce‐Fe‐O x, and then investigated the surface acidity and catalytic performance. The large amounts of sulfate species were formed over CF‐450 and CF‐550 while it was decomposed with further the increasing of calcination temperature, which resulted in the loss of surface acidity, causing a decrease in the catalytic activity over Ce‐Fe‐O x . Thereby, the CF‐450 catalyst showed the best catalytic activity and over 90% NO x conversion was obtained at 244–450 °C. Besides, the favored pore structure, more Fe 3+ active species, higher Ce 3+ concentration and the abundance of chemical adsorbed oxygen species, as well as the surface acid sites, would together contribute to the excellent catalytic activity of CF‐450 catalyst. Abstract : Ce‐Fe‐O x catalysts prepared by different calcination temperatures were investigated in the selectivity catalytic reduction of NO with NH3 . The sulfate species formed over Ce‐Fe‐O x at low calcination temperature (below 550 °C) treatment, resulting in the improvement of surface acidity and catalytic performance. While the calcination temperatures increased from 650 to 750 °C, causing the sulfate departure, which led to a decrease in the catalytic activity due to the loss of surface acidity.